Procesos urbanos y "ruralidad" en la periferia de la Zona metropolitana de la Ciudad de México - Cruz Rodríguez, María Soledad (El Colegio de México A.C., 2002)
The paper seeks to explore the relationship between urbanization and the agricultural sector of the Mexico City Metropolitan Zones. In its analysis, it considers the characteristics of urban expansion, the various interpretations of the relationship between the countryside and the city and the types of peripheral urbanization. The relationship between these elements sheds light on the important role played by the different types of land ownership and the peculiarities of the rural population in the definition of the new features of peripheral urbanization, which obliges one to reflect on the complexity of the inte- rrelationship between the urban and the rural in the metropolitan periphery.